Lobe Gene Frequency Identification Clinging and Eyebrows Connecting - Apriyani, Nella Dwi; Petriana, Fania (Tropical Genetics, 2024)
Study this done for know variety and frequency allele decider characteristics of the face and lobes, based on There is or not lobe attached and eyebrows continued, to students at SMAN 7 Sijunjung and SMAN 1 Sungai Limau. Study carried out on 500 samples probandus (250 people from students of SMAN 7 Sijunjung and 250 students of SMAN 1 Sungai Limau ) carried out observation in a way direct with fill in data forms, as well Analyzed probandus pedigree diagram. Research result show that as many as 71.2% of SMAN 7 Sijunjung students and SMAN 1 Sungai Limau students own characteristic lobe No attached, 28.8% have characteristic lobe attached, 64.6% have characteristic eyebrow No connect and 35.4% have characteristic eyebrow connect .